Analysis of cyclomobilityinitiatives in the 2021-2024 goal program of the municipality of São Paulo - Silva , Luciana Aparecida Ferreira da; Gallardo, Amarilis Lucia Casteli Figueiredo (Technical and Scientific Journal Green Cities, 2024)
Cycle mobility initiatives promoted by public management policies have generated debates about their effectiveness. This descriptive-exploratory work with a quantitative and qualitative approach has the main objective of evaluating compliance with the policies of the municipal management of the city of São Paulo for cycle mobility, based on the agreements of the 2021-2024 Target Program. Thus, it aims to contribute to academic production connected to the discussion and solution of contemporary problems of life in cities. The results reveal delays in the execution of agreed policies and great inequality in their implementation. The work points to the need to consider equity as a guiding element for the effectiveness of cyclomobility policies in their contribution to sustainable development in the São Paulo metropolis.
Keywords: Cyclomobility.; Public policy; Sustainable development